2016
DOI: 10.1016/j.jcrs.2016.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study using a new phacoemulsification system with surgical intraocular pressure control

Abstract: Drs. Solomon and Cionni are consultants to Alcon Research, Ltd., and received compensation for conduct of the study. Dr. Lorente received compensation for clinical work in the study. Mr. Fanney is an employee of Alcon Research, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 15 publications
0
60
0
7
Order By: Relevance
“…But it brings the effect of high perfusion pressure at the same time. Previous reports have reported that the instability of the uidics system during cataract surgery results in a longer operation time and an increase in CDE, which in turn will lead to longer recovery time and even poor visual function in postoperative patients [1][2]. So we wonder whether the uctuation of intraocular perfusion pressure during phacoemulsi cation affect fundus microcirculation and then affect the patient's postoperative vision.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…But it brings the effect of high perfusion pressure at the same time. Previous reports have reported that the instability of the uidics system during cataract surgery results in a longer operation time and an increase in CDE, which in turn will lead to longer recovery time and even poor visual function in postoperative patients [1][2]. So we wonder whether the uctuation of intraocular perfusion pressure during phacoemulsi cation affect fundus microcirculation and then affect the patient's postoperative vision.…”
Section: Discussionmentioning
confidence: 97%
“…Speci c perfusion is necessary to maintain the stability of the anterior chamber during cataract extraction. And this may cause transient intraocular pressure (IOP) uctuations during surgery which consequently result in corneal edema, poor visual acuity and longer time to recovery after surgery [1][2]. Whether the intraoperative perfusion and other surgical factors may cause fundus hemodynamic changes, especially macular microcirculation changes is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…The new devices with active fluidics, where the height of the irrigation bottle is not crucial, are the hope for the future. Active fluidics limits the need for high intraocular tension, while maintaining stability of the anterior chamber 17,18 . At the same time, it also contributes to improving the resulting parameters of the efficacy of phacoemulsification 19 .…”
Section: And In Cadaver Eyes By Khngmentioning
confidence: 99%
“…der kumulativen Energie. Der geringere Flüssigkeitsverbrauch soll auch das Endothel schützen [3,4]. Beim Ver- gleich der unterschiedlichen Phakohandgriffspitzen Kelman Tipp und Balanced Tipp konnte bei der mikrokoaxialen torsionalen Phakoemulsifikation kein Unterschied im Endothelzellverlust gezeigt werden [15], jedoch wurde die gleiche Flüssigkeitssteuerung verwendet und nicht auf den Unterschied der aktiven und der standardisierten Flüssigkeitssteuerung eingegangen.…”
Section: Diskussionunclassified